THE ESSENCE OF HUMAN BEINGS IN THE TAFSIR MAQĀL FI AL-INSĀN DIRĀSAH QUR’ĀNIYYAH BY BINT AL-SYATHI - Mutawakkil Faqih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Human being based on the term of insān is explained by mufassir as highly variable, there is a tendency on the side of human weakness in sexual passion, worldly pleasure aspect and directs its interpretation of the physical / body.The authors were interested in studying human nature human studies in the interpretation of Maqāl Fi al-Insān Dirāsah Qurāniyyah by Bintu al-Syāthī. The problems as follows, how methods, patterns and systematic interpretation and how does human nature by Bintu al-Syāthī perspective. According to Bintu al-Syāthī, the nature of human being in the Holy Qur’an. (a) Al-basyar is the sense of human being in material dimension, (b) Al-ins have meaning denoting kindness as opposed to savagery. (c) Al-Insān tends to interpretation the meaning of human being by the spiritual and social aspect.(d) Al-Nās for the descendants of Adam who showed human diversity and characteristics.